Effectiveness of measles vaccination and its associated risk factors and Complications among children under 5 in the slum areas of Karachi (Journal of Medical & Health Sciences Review, 2025)
Background: Measles remains a major cause of morbidity and mortality among children under five years in low-income settings globally, despite the availability of effective vaccination. Slum areas face amplified risk due to overcrowding, poor sanitation, and limited healthcare access.Objectives: To assess the effectiveness of measles vaccination, identify associated risk factors, and determine complications in children under 5 years residing in slum areas of Karachi.Methods: A cross-sectional study was conducted with 500 children aged 9 to 59 months from Karachi slums selected via stratified random sampling. Data on vaccination status, socio-demographics, risk factors, and measles complications were collected through interviews and health records. Descriptive statistics and inferential analyses including chi-square tests and logistic regression were performed.Results: Measles vaccination coverage was 68%. Vaccinated children had significantly lower incidence of measles infection (OR=0.28; 95% CI: 0.18-0.44; p